Consensus Statement on the Use of Intravenous Recombinant Tissue Plasminogen Activator to Treat Acute Ischemic Stroke by the Chinese Stroke Therapy Expert Panel. (27th May 2013) - Xu, An‐Ding; Wang, Yong‐Jun; Wang, David Z
Summary Background The last update of the consensus statement on intravenous recombinant tissue plasminogen activator (IV rt‐PA) for acute ischemic stroke (AIS) by the Chinese Stroke Therapy Expert Panel was published in 2006. Great progress has been made since then. Aim To provide another update on the new knowledge of IV rt‐PA for AIS since 7 years ago. Method In summer of 2012, the Chinese Stroke Therapy Expert Panel was reconvened. New publications on the use of IV rt‐PA for AIS were reviewed. In addition, all newly published consensus and guidelines from other countries were reviewed. The 2006 version of Chinese Consensus was then updated. Results There is now clinical evidence to support the use of IV rt‐PA between 3 and 4.5 h after the onset with several exclusion criteria. More studies are needed to provide the evidence for IV rt‐PA use beyond 4.5 h. There is benefit giving IV rt‐PA within 3 h to patients who are older than 80 and in patients with ongoing atrial fibrillation. Patients with INR<1.7 while on warfarin, minor strokes, rapid improving strokes and severe strokes should be treated and can all be benefited from IV rt‐PA. Discussion Since IV rt‐PA was initially recommended in 1996, there is now more evidence support its use, efficacy and safety. The treatment time window is also being expanded. More public education on stroke recognition are needed so many stroke patients may benefit from the treatment. Conclusion The 2013 version of Chinese IV rt‐PA consensus contains the most up‐to‐date information on the use of IV rt‐PA for AIS. It will be a useful tool and guideline to provide appropriate thrombolytic therapy to stroke patients who meet the criteria.